2007
DOI: 10.1016/j.cmet.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of BCATm in Mice Leads to Increased Energy Expenditure Associated with the Activation of a Futile Protein Turnover Cycle

Abstract: Leucine is recognized as a nutrient signal; however, the long-term in vivo consequences of leucine signaling and the role of branched-chain amino acid (BCAA) metabolism in this signaling remain unclear. To investigate these questions, we disrupted the BCATm gene, which encodes the enzyme catalyzing the first step in peripheral BCAA metabolism. BCATm(-/-) mice exhibited elevated plasma BCAAs and decreased adiposity and body weight, despite eating more food, along with increased energy expenditure, remarkable im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
320
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(351 citation statements)
references
References 60 publications
27
320
3
1
Order By: Relevance
“…Total RNA (1 μg) was reverse-transcribed using Superscript II Reverse Transcriptase (Invitrogen, Carlsbad, CA, USA) with oligo-d(T) [12][13][14][15][16][17][18] as primer. After reverse transcription, the same batch of diluted cDNA was subjected to real-time polymerase chain reaction (PCR) to amplify target genes.…”
Section: Glp-1 Release Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA (1 μg) was reverse-transcribed using Superscript II Reverse Transcriptase (Invitrogen, Carlsbad, CA, USA) with oligo-d(T) [12][13][14][15][16][17][18] as primer. After reverse transcription, the same batch of diluted cDNA was subjected to real-time polymerase chain reaction (PCR) to amplify target genes.…”
Section: Glp-1 Release Studymentioning
confidence: 99%
“…As regulators of protein metabolism, branched-chain amino acids (BCAAs; leucine, isoleucine, and valine) have also been reported to improve glucose and cholesterol metabolism [13,14] and control appetite [15]. A study by Bowen et al [16] suggested that the protein component of dairy appears to be more important for weight loss than calcium in over-weight adults.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, exercise decreased BCAA in db mice more than food restriction in db mice. In db mice, branched-chain a-keto acids such as isovaleric acid showed lower excretion in urine [32], indicating the slow degradation and transport of BCAA in WAT and SM, which are thought to play a role in BCAA metabolism [26,27,33]. The gene expressions of BCAT2, SLC3A2, and SLC7A5, the responsible genes in BCAA degradation and transport, were not altered under exercise conditions in our models, except BCAT2 in SM (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Real-time quantitative PCR was performed using SYBR-green on a TAKARA detection system (TAKARA, Shiga, Japan) under the conditions recommended by the manufacturer. The primary sequences of the genes are shown in supplementary Table 1 [26,27]. The relative level of mRNA was calculated using cycle time (Ct) values, which were normalized against the value of btubulin.…”
Section: Gene Expressionsmentioning
confidence: 99%
“…Theoretically, leucine is capable of modulating insulin signaling through the mammalian target of rapamycin (mTOR) 3 and S6K-mediated serine phosphorylations of IRS1/2 (3,21). It is noteworthy that supplementation of leucine can increase insulin sensitivity in obese animals (13,14), and the increased level of branched chain amino acids by knocking out the ratelimiting enzyme that catabolizes branched chain amino acids is associated with increased and not decreased insulin sensitivity (22). The increased insulin sensitivity by branched chain amino acids can be at least partially explained by decreased food intake and elevated energy expenditure (13,14,22).…”
mentioning
confidence: 99%